How does climate exacerbate root causes of conflict in Senegal? An econometric analysis - Villa, Victor; Belli, Anna; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Senegal, using a two-stage econometric approach. The findings show how rising temperatures and rainfall anomalies combined with nutritional insecurity can increase the likelihood of conflict in Senegal.